Prognostic implications of preoperative, postoperative, and dynamic changes of alpha-fetoprotein and des-gamma (γ)-carboxy prothrombin expression pattern for hepatocellular carcinoma after hepatic resection: a multicenter observational study - Tang, Shi-Chuan; Wu, Ye-Ye; Lin, Zhi-Wen; Chen, Qing-Jing; Luo, Cong; Li, Yun-Tong; Fu, Jun; Zheng, Li-Fang; You, Peng-Hui; You, Song; You, Wu-Yi; Lin, Ke-Can; et al. (Frontiers in Oncology, 2024)
The utility of pre-and post-operative alpha-fetoprotein (AFP) and des-gamma (γ)carboxy prothrombin (DCP) expression patterns and their dynamic changes as predictors of the outcome of hepatic resection for hepatocellular carcinoma (HCC) has yet to be well elucidated.: From a multicenter database, AFP and DCP data during the week prior to surgery and the first post-discharge outpatient visit (within 1-2 months after surgery) were collected from patients with HCC who underwent hepatectomy. AFP-DCP expression patterns were categorized according to the number of positive tumor markers (AFP ≥20ng/mL, DCP ≥40mAU/mL), including double-negative, single-positive, and double-positive. Changes in the AFP-DCP expression patterns were delineated based on variations in the number of positive tumor markers when comparing pre-and post-operative patterns.Results: Preoperatively, 53 patients (8.3%), 337 patients (52.8%), and 248 patients (38.9%) exhibited double-negative, single-positive, and double-positive AFP-DCP expression patterns, respectively.Postoperatively, 463 patients (72.6%), 130 patients (20.4%), and 45 patients (7.0%) showed doublenegative, single-positive, and double-positive AFP-DCP expression patterns, respectively. Survival analysis showed a progressive decrease in recurrence-free (RFS) and overall survival (OS) as the number of postoperative positive tumor markers increased (both P < 0.001). Multivariate analysis showed that postoperative AFP-DCP expression pattern, but not preoperative AFP-DCP expression pattern, was an independent risk factor for RFS and OS. Further analysis showed that for patients with positive preoperative markers, prognosis gradually improves as positive markers decrease postoperatively. In particular, when all postoperative markers turned negative, the prognosis was consistent with that of preoperative double-negative patients, regardless of the initial number of positive markers.: AFP-DCP expression patterns, particularly postoperative patterns, serve as vital sources of information for prognostic evaluation following hepatectomy for HCC. Moreover, changes in AFP-DCP expression patterns from pre-to post-operation enable dynamic prognostic risk stratification postoperatively, aiding the development of individualized follow-up strategies.